The Subgenus Forcipomyia (Metaforcipomyia) In Argentina (Diptera, Ceratopogonidae) - Marino, Pablo Ignacio (2001)
Two new species of the subgenusForcipomyia (Metaforcipomyia), from Argentina,F. (M.) william.si and F. ( M.) galliarii, are described and iJlustrated. In addition,F. ( M.) cerifera Saunders, l 956 is redescribed and fi recorded for Argentina.